ANALISIS KESIAPAN PENGIMPLEMENTASIAN EDUROAM DI UIN SUNAN KALIJAGA - Siregar, Maria Ulfah; Amalia, Alifah; Sugiantoro, Bambang (JURNAL TEKNIK INFORMATIKA, 2020)
This research is based on the existence of Eduroam in academia world which offers the easiness on managing data through internet. Inevitably, UIN Sunan Kalijaga as one of big campus in terms of number of population of academicians and the usage of internet in its area, has not joined in a group of institutions that implemented Eduroam. Through this research we aim to give brainstorming to academicians of UIN Sunan Kalijaga of the existence of Eduroam, then we will conclude the feasibility of implementing Eduroam on UIN Sunan Kalijaga. As guidances for this research are two hypotheses that we built. Our research method is conducting survey and interview to two domestic institutions which implemented Eduroam. It is followed by distributing online internal questionnare in UIN Sunan Kalijaga to do the brainstorming and collecting data. These data then were analyzed statistically to get the descriptive statistic, correlation and proved the hypotheses. Based on our analysis, it is found that there is a strong relation between the knowledge of Eduroam and the intention to join Eduroam, and a strong relation between the frequency of the usage of internet and the intention to join Eduroam. Therefore, we claim that it is feasible to implement Eduroam on UIN Sunan Kalijaga, by first improving the quality and quantity of the internet connection facilities on UIN Sunan Kalijaga.